Teaching-service partnership in the unified health system: implementation of outpatient pharmacotherapeutical follow-up - Marlon Silva Tinoco (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2019)
Background: The irrational medicine use is a public health problem and, in this context, the pharmacist assists in improving the use of drugs, reducing the risks of morbidity and mortality and the costs of pharmacotherapy. Data referring to the pharmacy service highlight the importance and the emerging need of insertion of this professional in the health teams.